THE FORMULATION OF TOUR SERVICE PRICE WITH ACTIVITY-COST PLUS PRICING METHOD (CASE STUDY AT PT. AIRLANGGA GLOBAL TRAVELING) - Ni Made Ayu Lakshmi Prastiti; I Made Narsa; Niluh Putu Dian Rosalina Handayani Narsa (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
This study aims to determine the formulation of the sell price for service of tour package at travel companies. This research was conducted at PT Airlangga Global Traveling Surabaya. The analytical method used in this study is a comparative descriptive, is the analysis of the curreny selling price of tour package services, determining the cost method based on activity cost plus pricing, then comparing the selling price of tour package services based on current methods with activity cost plus pricing. The result of this research showed that the calculation of the selling price of the company method is too high when it compares with using the activity cost plus pricing method. This is due to the imposition of indirect cost on each of the tour package service products that have been able to allocate cost appropriately based on the consumption of each activity. This research contributes to PT Airlangga Global Traveling itself, that they sould be allocate indirect cost using Activity Cost Plus Pricing to formulate the right selling price. Other than that, this research also contributes to the literature history regarding TDABC which is still very rarely written in detail case step-by-step.